Skeleton runner roughness and surface contact area influence on sliding ability: Field experiments - Lungevics, J.; Jansons, E.; Gross, K. A. (2019)
Scientists and sport athletes are constantly seeking for the methods which could improve surface sliding ability on ice. Modifications of contact area and surface roughness are relatively easy but not yet fully understood methods for sliding ability improvements. This research contains information of how one can perform on-field experiments with skeleton sleigh to determine the influence of surface contact area and roughness on sliding ability. Two types of surface roughness i.e. polished (3000 grain sandpaper) and scratched (600 grain sandpaper) are compared using three different contact areas. Obtained data showed that rougher surfaces tend to slide faster if contact area is larger but the effect reverses if contact area is reduced.